Hubungan Karakteristik Akseptor KB Baru Dengan Penggunaan Non Metode Kontrasepsi Efektif Terpilih - Rismawati, Rismawati; Kasmiati, Kasmiati (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
Efforts to reduce the population growth rate are to control the birth rate through family planning programs. This study aimed to determine the relationship between the characteristics of new family planning acceptors and the use of Selected Effective Contraceptive Methods. This study is descriptive-analytic with a cross-sectional approach. The number of samples in this study was 49 samples. The sampling technique used was total sampling—research data analysis using Chi Square analysis and Odd Ratio. The results showed a relationship between age and contraceptive use of contraceptives Non Selected Effective Methods p value 0.002 and OR = 10.875. There is a relationship between parity and the use of Non-Effective Contraceptive Methods Selected p value 0.043 and OR = 5.667. There is no relationship between education and the use of Selected Effective Contraceptive Methods, with a p-value of 0.210 and OR=0.387. All parties are expected to improve, understand, and provide counseling on the use of non-MKET family planning so that each acceptor can choose the right type of family planning.